Fantasy as an instrument in child behavioral therapy (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
Among other means, child psychotherapy uses fantasy that permits to identify feelings, rules and contingencies which maintain inadequate behaviors. This research aims to compare the information in scientific literature to psychologists' opinion about what abilities and knowledge are necessary to an efficient intervention using the fantasy as an auxiliary to understand and plan behavioral changes. The methodology applied is the survey of four interviews made to psychologists that work with children and their relatives in the clinical context. The data were compared to information from the scientific literature and the investigators evaluated issues that could be analyzed in future researches. Literature is confirmed by the psychologists’ statements about the relevance of theoretical knowledge, strategies of learning, functional analysis, and empathy. Nor consistence neither agreement about the definition of fantasy was found among the psychologists. Such definition is not found in literature either. Future researches on fantasy are suggested.